(untitled) (Sains Humanika, 2013)
The introduction of the Malaysian University English Test (MUET) has sparked the urgency to train pre-university students to communicate effectively and spurred the interest of language researchers to develop speaking skills among students in Malaysia. New methods and strategies are attempted to overcome various communication problems, and ease communication especially in the discussion component of MUET. However, due to its spontaneity, speaking remains the most difficult skill to acquire. This paper presents findings of an ongoing research on compensation features for task fulfilment in discussions. It discusses instances of how compensation features, in particular corrections and alterations, are used in discussions. This paper highlights such features as used by pre-university students in discussions which involve self-correction/self-repair, false start, repetition and restructuring/rephrasing.